Environment &​ landscape (Seoul, Korea, 2005)
Contents: Apartment. Universiade athletes' Village, Daegu; Samsung reamian, Seocho-dong; Lotte spa castle, Dogok-dong;... .
Keywords: Thiết kế cảnh quan,Landscape design